Evaluation of cytotoxic and genotoxic activity of fungicide formulation Tango® Super in bovine lymphocytes. (January 2017) - Schwarzbacherová, Viera; Wnuk, Maciej; Lewinska, Anna; Potocki, Leszek; Zebrowski, Jacek; Koziorowski, Marek; Holečková, Beáta; Šiviková, Katarína; Dianovský, Ján
Abstract: Tango ® Super is a two-compound fungicide formulation widely employed in grain protection. However, details of Tango ® Super effects on cell cultures have not been fully investigated. In this study, bovine lymphocytes were exposed to a concentration range 0.5; 1.5; 3; 6; and 15 μg mL −1 for 4 h to assess the cytotoxicity and genotoxicity of the fungicide. Our experiments revealed that this fungicide treatment reduced cell viability, decreased cell proliferation and provoked apoptotic cell death. Cell cycle analysis showed predominant accumulation of cells in the G0 /G1 phase of the cell cycle. The fungicide was able to induce mitochondrial superoxide production accompanied by elevated levels of carbonylated proteins and changes in the lipid membrane composition. The fungicide did not induce micronuclei production, but stimulated both DNA double-strand breaks and the formation of p53 binding protein, which is accumulated during the DNA repair process at the site of double-strand breaks. Based on the obtained data we suppose that the fungicide-induced DNA damage is the result of oxidative stress, which may contribute to higher occurrence of apoptotic cell death. Because ergosterol biosynthesis-inhibiting fungicides are widely used in agriculture to ensure higher crop yields and may cause health impairment of animals and humans, there is a need for further testing to elucidate their potential genotoxic effects using in vivo and/or in vitro systems. Graphical abstract: Highlights: Tango ® Super cyto- and genotoxicity was examined in cultured bovine lymphocytes. The fungicide provoked apoptotic cell death and mitochondrial superoxide production. Double-strand breaks and p53 binding protein were induced as a result of DNA damage. The fungicide-induced DNA damage was the result of oxidative stress. Oxidative stress may contribute to a higher occurrence of apoptotic cell death. Abstract : Ergosterol biosynthesis-inhibiting fungicides are able to induce DNA damage as a result of oxidative stress, which may contribute to higher occurrence of apoptotic cell death.